Rusia, pasado, presente Y futuro - Akhmetova, Elmira (La Vanguardia, 2015)
When we hear the expression ‘European Muslim’, the first thing that usually occurs in our minds is the Muslims of the West, mainly immigrants with Muslim backgrounds or white Western converts. This short essay narrates another image of ‘European Islam’: Islam on Russian soil. The Russian Federation (RF) is one of the most diverse countries of Europe, where Muslims and Christians are living side by side more or less peacefully for many centuries. Islam in Russia is not a religion of postcolonial immigration, nor is it a manifestation of the recent acceleration of globalisation and cultural exchange. Unlike other Muslim minorities in Europe, Muslims in Russia are indigenous citizens of the country who live in their native land. In 2000, the Muslims of Russia celebrated fourteen centuries of Islam on Russian soil. Throughout these centuries, Muslims took an active part in building what we call today ‘Russian civilisation’.